Toward psychologies of liberation - Watkins, Mary 1950-; Shulman, Helene (London Palgrave Macmillan, 2010)
A presentation of the theoretical foundation and participatory methodologies of psychologies of liberation that are emerging on every continent. The book proposes a radical interdisciplinary reorientation of psychology to aid in the creation of participatory and dialogical spaces for critical understanding and creative restoration.
Part 1. Compass points -- Beyond universalism -- Local regeneration -- Beyond ideology -- Dialogue -- Beyond development -- Liberation -- Part 2. Psychic wounds of colonialism and globalization -- Symptoms and psychologies in the context of culture -- From bystanding to engaged witness bystanding -- Pathologies of perpetration -- Mourning and witness after collective trauma -- Part 3. Springs for creative restoration -- Rupture and hospitality -- Non-subjects and nomadic consciousness -- Dialogue -- Part 4. Participatory practice for regeneration -- Communities of resistance -- Libertory arts and imagination -- Critical participatory action research -- Placing dialogue ethics at the centre of research -- Dreams of reconciliation and restoration -- Afterword: Tikkun Olam: The Restoration and Repair of the World.
First published: 2008.
Includes bibliographical references (pages 341-357) and index.
Keywords: Psychology; Globalization; Oppression (Psychology).; Autonomy (Psychology).; Liberty